MR findings of primary ovarian granulosa cell tumor with focus on the differentiation with other ovarian sex cord-stromal tumors - He Zhang; Hongyu Zhang; Shouxin Gu; Yanyu Zhang; Xuefen Liu; Guofu Zhang (BMC, 2018)
Abstract Background To describe magnetic resonance imaging (MRI) features of ovarian granulosa cell tumors (OGCTs) and compare with other sex cord-stromal tumors (OSCs) in ovary. Methods MR findings of 18 patients with surgically confirmed ovarian granulosa cell tumor were retrospectively reviewed by two radiologists with consensus reading. All MR examinations were prospectively performed within one month. Clinical and imaging characteristics of OGCTs were evaluated and compared with OSCs (control group). Results In 18 patients, 20 ovarian granulosa cell tumors were detected on MRI. Sixteen tumors appeared as solid or mostly solid mass (16/20), while 4 tumors as cystic mass. Pathological pelvic fluid was detected in 1 OGCT (1/18) and 11 OSCs (11/34) (p = 0.031).On T2 weighted imaging (T2WI), most of OGCTs displayed hyperintense signal and mixed signal (19/20); on T1 weighted imaging (T1WI), 11 OGCTs (11/20) displayed similar signal as on T2WI imaging. The lesion signal between OGCT and OSC differed significantly on both T1WI (p = 0.017) and T2WI (p = 0.002). Tumoral bleeding was detected in 6 OGCTs on MRI. On diffusion weighted imaging (DWI) images, OGCTs mostly appeared as high signal (16/20). Average apparent diffusion coefficient (ADC) value derived from DWI images in the OGCT group (0.84 ± 0.26× 10− 3 mm2/s was less than the control group (1.22 ± 0.47 × 10− 3 mm2/s) with statistical difference (p = 0.002). Conclusions MRI could provide important information in OGCT diagnosis. ADC value might be useful in differentiating OGCT from OSC.